Crystallinity of hydroxyapatite powders from acid washed and thermally-treated tilapia bones - Butanas, Bienvenido M., Jr (CMU Journal of Science: the official Scientific Journal of Central Mindanao University, 2017)
This paper presents the production of quality hydroxyapatite (HAp) powders from tilapia bones using thermal treatment. Hydroxyapatite was successfully synthesized by calcination of 0.5M HCI pre-treated tilapia bones. Powder X-ray diffraction (XRD) revealed the nano-crystalline hexagonal structure of Hap powders. Peaks associated with impurities such as hydrates and carbonates decreased and vanished along with the coalescence of particles as calcination temperature increased. XRD results also showed better crystal formation at 800 and 900ºC. The synthesized HAp powder in this study conformed well to the properties of biological apatites.